PENGARUH KEPEMILIKAN SAHAM INSTITUSI, KEPEMILIKAN SAHAM PUBLIK, KEBIJAKAN DIVIDEN, STRUKTUR ASET, DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Niken Anindhita; Yuneita Anisma; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Purpose of this study was to examine the effect of Institutions Share Ownership, Public Share Ownership, Dividend Policy, Assets Structure, And Profitability On Debt Policy In Manufacturing Companies of Indonesia Stock Exchange In 2012-2014. The population in this study is all manufacturing companies engaged in in Indonesia Stock Exchange. The sampling technique is purposive sampling, a sampling method with certain considerations. The data used in this research is secondary data. Sources of data in this study are company's financial reports such as Balance Sheet, Income Statement Year 2012-2014. The analytical method used in this research is multiple regression analysis. Based on the data collected and testing has been done on the problem by using regression analysis method, it can be concluded: 1) There is no significant effect of Institutional Share Ownership on Debt Policy. It means that changes in Institutions Share Ownership do not lead to any significant change in the Debt Policy. 2) There is no significant effect of Public Share Ownership on Debt Policy. It means that changes in Public Share Ownership do not lead to any significant change in the Debt Policy. 3) There is no significant effect of Dividend Policy on Debt Policy. It means that changes in Dividend Policy do not lead to any significant change in the Debt Policy. 4) Asset Structure has a significant effect on Debt Policy. It means that the greater Assets structure, the greater the Debt Policy. 5) Profitability has a significant effect on Debt Policy. It means that the greater Profitability, the greater the Debt Policy.Keywords: Institutions Shareholding, Public Shareholding, Dividend Policy, Assets Structure, Profitability and Debt Policy